Neuroprotective and vision‐protective effect of preserving ATP levels by AMPK activator. Issue 4 (24th February 2020) - Kawashima, Hirohiko; Ozawa, Yoko; Toda, Eriko; Homma, Kohei; Osada, Hideto; Narimatsu, Toshio; Nagai, Norihiro; Tsubota, Kazuo
Abstract: Progression of blinding diseases, such as age‐related macular degeneration, is accelerated by light exposure. However, no particular intervention is applied to the photostress. Here, we report neuroprotective effects of the adenosine monophosphate (AMP)‐activated protein kinase (AMPK) activator, 5‐Aminoimidazole‐4‐carboxamide ribonucleotide (AICAR), on light‐induced visual function impairment, photoreceptor disorders and death in mice. Increase in retinal ATP levels in response to photostress was transient, because oxygen consumption rate (OCR) and cytochrome c oxidase (CcO) activity were reduced under photostress. However, AICAR treatment preserved OCR, CcO activity, and high levels of retinal ATP after light exposure. AMPK knockdown in the photoreceptor‐derived cell line revealed that AMPK targeted CcO activity. Further, our data indicated that photostress reduced mitochondrial respiratory function and ATP levels, while AICAR treatment promoted neuronal survival and retained visual function, stabilizing ATP levels through preserved CcO activity. The current study has provided proof of concept for providing cells with sufficient energy to promote cell survival in the presence of cellular stress. This is in contrast to the previous reports which primarily investigated therapeutic approaches to suppress stress signals. Hence, stabilization of the ATP supply may serve as a novel therapeutic approach to support tissue survival under stress and prevent neurodegeneration.